Solar cell module - SHAO PING; WU YUFEI; YU HAIBEI; SHAO RONGSHUN; LI HAIYANG; WU XIANGFA; ZHOU WEIQIANG (2014)
The utility model provides a solar cell module. The solar cell module comprises a TPE backboard, an ethylene-vinyl acetate copolymer (EVA) adhesive film laminated on the TPE backboard, a battery piece laminated on the EVA adhesive film, a polyolefin elastomer (POE) antioxidant adhesive film laminated on the battery piece, and coated glass laminated on the POE antioxidant adhesive film. The POE antioxidant adhesive film has excellent weather resistance, ageing resistance, anti-static electricity capacities, potential induced degradation (PID) resistance, and a low yellowness index, so the aging rate of the solar cell module is reduced, and the service life of the solar cell module is raised. Moreover, the coated glass is adopted to replace ordinary toughened glass, so the light utilization efficiency is greatly raised, the power of the solar cell module is increased, the PID resistance of the solar cell module is also enhanced, and the service life of the solar cell module is further prolonged.